(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:In the second half of the forties of the twentieth century, a group of notables and merchants of the Faili Kurds in Baghdad embarked on the initiation of the establishment of the National Faili School Association in 1946, which took upon itself the responsibility of establishing the Faili schools in Baghdad and supervising their management and financing in the region in which the majority of the Faili Kurdish population resided. In accordance with its cultural and educational orientations aimed at raising the scientific, moral and religious level of its children in society and giving them modern education. The educational activity of the Faili Association resulted in the establishment of its first day schools in Baghdad in 1946 under the name (Al-Faili Primary School for Boys), and a few years later another primary school was added to it in its evening section, while the association began by 1956 to establish (the Faili Evening Middle School for Boys) and in the year 1962 The preparatory section was added to it to become an integrated secondary school that includes all educational stages under the name (Al-Faili Evening High School for Boys). Faili schools continued to exist until 1974 after the Baath authority nationalized all private and foreign schools on February 7, 1974 and converted them into government schools after changing their national names. Martyr Suleiman evening for boys.Keywords: (Faili School - Society - Ministry of Education).